A micro-sociological analysis of homegrown violent extremist attacks in the UK in 2017. Issue 1 (2nd January 2019) - McCleery, Martin; Edwards, Aaron
ABSTRACT: The academic literature on terrorism largely ignores micro-sociological explanations of violence. This is especially true in relation to the research concerning Homegrown Violent Extremists (HVE). This article provides a micro-sociological analysis of four high-profile terrorist attacks that occurred in the British cities of London and Manchester in 2017, which were carried out with deadly effect by HVE. The main focus of the article is the micro-dynamics surrounding each violent episode, although the article also recognizes the importance of the meso factors and macro motivations underpinning these violent acts. One of the central assertions of this article is that most humans dislike and are not particularly good at violence. As such, it seeks to understand how the individuals involved in these attacks could partake in such violence. It argues that most individuals must employ what we refer to as the principle of Attacker Advantage to commit violent acts, regardless of other factors and motivations.